Troubleshooting in an IVF Laboratory - Keshav Malhotra (Fertility & Reproduction, 2023)
In the realm of assisted reproductive technology, troubleshooting within an in vitro fertilization (IVF) laboratory is of paramount importance to ensure successful outcomes. FMEA is a proactive methodology used to identify potential failure modes in laboratory processes, assess their possible effects, and prioritize interventions to prevent or mitigate them. In the context of IVF, FMEA aids in recognizing critical steps prone to errors, such as sample mishandling or equipment malfunctions. By quantifying the probability and severity of failures, FMEA allows laboratories to allocate resources judiciously and implement corrective measures that reduce the likelihood of adverse events. Root cause analysis (RCA) is a retrospective technique employed to delve into the underlying causes of anomalies or failures that have already occurred. In the IVF laboratory, RCA helps uncover the root reasons for unsuccessful procedures, like embryo implantation failure. This analysis aids in identifying both immediate triggers and underlying systemic issues, paving the way for targeted improvements to enhance overall success rates. By plotting key performance indicators over time, IVF laboratories can detect deviations from established norms. This enables swift corrective actions before deviations result in compromised outcomes. Control Charts thus offer a dynamic tool for monitoring laboratory processes, maintaining consistency, and swiftly addressing unexpected fluctuations. By systematically preventing potential failures, investigating root causes, and dynamically monitoring processes, IVF laboratories can improve their success rates, enhance patient experiences, and contribute to the advancement of assisted reproductive technologies.